Meningothelial Meningioma Component in a Prepubertal Testicular Teratoma. (21st January 2020) - Sinha, Ruchi; Kumari, Madhu; Sinha, Ranwir Kumar; Kumar, Bindey
Abstract : Teratomas are nonseminomatous germ cell tumors composed of elements derived from more than one germinal layers (endoderm, mesoderm, and ectoderm). Malignant transformation of teratoma in the testis is well known; however, benign somatic neoplasm arising in a testicular teratoma is a rare occurrence. We report a case of meningothelial variant of meningioma arising in a pure and mature teratoma of the testis in a 5-year-old boy. Immunohistochemistry was positive for epithelial membrane antigen and vimentin. To our knowledge, this is the first report of meningothelial meningioma in a prepubertal testicular teratoma.